2022
DOI: 10.3390/healthcare10122369
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude towards Obstructive Sleep Apnea among Primary Care Physicians in Northern Regions of Saudi Arabia: A Multicenter Study

Abstract: Obstructive sleep apnea (OSA) is a serious and often underreported condition, despite its highly prevalent distribution. Primary care physicians (PCPs) play an integral role in screening and managing patients with a high risk of developing OSA. This northern Saudi Arabian cross-sectional survey assessed the knowledge and attitude towards OSA among 264 randomly selected PCPs using the OSA Knowledge and Attitude (OSAKA) questionnaire. Among the participating PCPs, 43.9% and 45.1% had low scores in the knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…The participants exhibited a low to moderate degree of overall knowledge and awareness, with just a minority displaying a high level of knowledge and awareness. Similar results were reported by recent studies conducted in Saudi Arabia and Ecuador, which revealed that the mean score of the respondents was approximately 10 out of 18 [ 22 , 24 ]. On the contrary, a few alternative studies have documented somewhat higher average knowledge scores among the participants [ 16 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The participants exhibited a low to moderate degree of overall knowledge and awareness, with just a minority displaying a high level of knowledge and awareness. Similar results were reported by recent studies conducted in Saudi Arabia and Ecuador, which revealed that the mean score of the respondents was approximately 10 out of 18 [ 22 , 24 ]. On the contrary, a few alternative studies have documented somewhat higher average knowledge scores among the participants [ 16 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…Higher levels of knowledge and awareness were observed among females, non-Saudi participants, those who specialized in internal medicine, pediatrics, and otolaryngology, persons with fewer than 10 years of experience, and specialists and consultants. The results of this study align with prior research that has demonstrated discrepancies in OSA knowledge and awareness according to demographic attributes [ 22 , 27 ]. The authors emphasize the need to take into account these variables during the development of training interventions and customize them to suit the particular requirements of distinct healthcare professional cohorts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Saudi Arabia likely has a high prevalence of sleep disorders, including OSA, owing to the increasing prevalence of obesity and diabetes [9,10]. Some Saudi studies have evaluated sleep disorder and OSA prevalence in Riyadh (21%), and the eastern province (26%) [11,12].…”
Section: Introductionmentioning
confidence: 99%